2023
DOI: 10.1162/netn_a_00292
|View full text |Cite
|
Sign up to set email alerts
|

Larger lesion volume in people with multiple sclerosis is associated with increased transition energies between brain states and decreased entropy of brain activity

Abstract: Quantifying the relationship between the brain’s functional activity patterns and its structural backbone is crucial when relating the severity of brain pathology to disability in multiple sclerosis (MS). Network control theory (NCT) characterizes the brain’s energetic landscape using the structural connectome and patterns of brain activity over time. We applied NCT to investigate brain state dynamics and energy landscapes in controls and people with MS (pwMS). We also computed entropy of brain activity and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
1
8
1
Order By: Relevance
“…This aligns with findings from prior research on shifts in connectivity states in MS. 15,45,46 The same might be true for the detected increase in control energy for CI patients, as recent work showed that MS patients with physical disability required more control energy compared to non-disabled patients. 21 In contrast to that finding, we did not observe a relationship between physical disability and transition control energy in this study, possibly as our cohort had longer disease durations where disability mechanisms might be different. Interestingly, the transition control energy was particularly relevant for information processing speed and verbal fluency which suggests that transition control energy might be related to shared cognitive processes, such as cognitive flexibility.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This aligns with findings from prior research on shifts in connectivity states in MS. 15,45,46 The same might be true for the detected increase in control energy for CI patients, as recent work showed that MS patients with physical disability required more control energy compared to non-disabled patients. 21 In contrast to that finding, we did not observe a relationship between physical disability and transition control energy in this study, possibly as our cohort had longer disease durations where disability mechanisms might be different. Interestingly, the transition control energy was particularly relevant for information processing speed and verbal fluency which suggests that transition control energy might be related to shared cognitive processes, such as cognitive flexibility.…”
Section: Discussioncontrasting
confidence: 96%
“…43 Parameter choice is still a topic of debate, however, particularly for the arbitrary choice of a control horizon, which is why we optimized this parameter using a data-driven approach (see eMethods 1). 21 Despite these challenges, the current framework offers an exciting opportunity and generalizable approach to study and develop personalized treatment of cognitive impairment in MS by identifying optimal target areas for transcranial magnetic stimulation or for tailoring pharmacological interventions. 48,49 Furthermore, although fine-grained temporal scales can increase noisiness of windowed connectivity (i.e., short windows), the current approach utilizes information (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, correlations of SC and FC are moderate at best. Understanding the relationship between SC and FC is key to deciphering how the brain's physical structure supports its dynamic functions and may offer insights into the neural mechanisms underlying behavior, injury or disease, and recovery [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…27 In MS, a relevant measure, the energy required by brain state transitions, has proven to be useful for distinguishing patients in different disability status. 28 However, whether network controllability measures alter in people with MS and whether these changes (if exist) differ between patients with different status of cognition remain unclear.…”
Section: Introductionmentioning
confidence: 99%